Dynamic Changes of Cytoskeleton-Related Proteins Within Reward-Related Brain Regions in Morphine-Associated Memory - Yang, Xixi; Wen, Yichong; Zhang, Yuxiang; Gao, Feifei; Yang, Jingsi; Yang, Zhuojin; Yan, Chunxia (Frontiers in Neuroscience, 2021)
Drug-induced memory engaged complex and dynamic processes, and was coordinated at multiple reward-related brain regions. A spatiotemporal molecular mechanisms underlying different addiction phases remained unknown. We investigated the role of β-actin, as well as its potential modulatory protein Arc/Arg3.1 and ERK, in reward-related associative learning and memory using morphine-induced conditioned place preference (CPP) in mice. CPP was established by alternate morphine (10 mg/kg) injections, extinguished after a 10-day extinction training, while withdrawal group failed to extinguish without training. In the nucleus accumbens (NAc), morphine enhanced the level of β-actin and Arc only during extinction, while p-ERK1/2 was increased during both CPP acquisition and extinction phases. In the dorsal hippocampus, morphine induced an up-regulation of p-ERK only during extinction, while p-β-actin was elevated during both CPP establishment and extinction. In the dorsal hippocampus, Arc was elevated during CPP formation and suppressed during extinction. Compared with NAc and dorsal hippocampus, dynamic changes in the medial prefrontal cortex (mPFC) and caudate putamen (CPu) were not very significant. These results suggested region-specific changes of p-β-actin, Arc/Arg3.1 and p-ERK1/2 protein during establishment and extinction phases of morphine-induced CPP. These findings unveiled a spatiotemporal molecular regulation in opiate-induced plasticity.